Bone-targeted delivery of senolytics to eliminate senescent cells increases bone formation in senile osteoporosis. (February 2023) - Xing, Xiaotao; Tang, Qi; Zou, Jiaojiao; Huang, Haisen; Yang, Jian; Gao, Xin; Xu, Xun; Ma, Shixing; Li, Maojiao; Liang, Cheng; Tan, Lin; Liao, Li; et al.
Abstract: Systemic elimination of senescent cells using senolytic drugs presents therapeutic effects on age-related diseases, including senile osteoporosis. However, low bioavailability and potential side effects of senolytics restrict clinical application. Therefore, we developed a bone-targeted delivery system for senolytics to effective treatment of senile osteoporosis. In this study, quercetin was screened out as the ideal senolytics for eliminating senescent BMSCs. Treatment of quercetin efficiently decreased the senescence markers in senescent BMSCs models. After treatment with quercetin in vitro, cell mitosis and calcification staining assay confirmed that the proliferation and osteogenesis of the senescent BMSCs populations were enhanced. To enhance the effectiveness and minimize the side effect of treatment, liposomes decorated with bone affinity peptide (DSS)6 were constructed for bone-targeted delivery of quercetin. After administration of liposomes loading quercetin in two aged mice models, histological and cellular analysis confirmed that bone-targeted treatment with quercetin efficiently eliminated senescent cells in bone, restored the function of BMCSs, and promoted bone formation in aged mice models when compared to non-targeted treatment. Taken together, the bone-targeted delivery of senolytics efficiently eliminates senescent cells to recover bone mass and microarchitecture, showing an effective treatment for senile osteoporosis. Statement of Significance: Senile osteoporosis, a common and hazardous chronic disease, has been still lacking effective therapy. How to effectively eliminate the hazards of senescent cells in skeleton to bone formation remains challenge. In this study, quercetin was screened out as the ideal senolytic drug for senescent BMSCs and could effectively eliminated senescent BMSCs to restore the cellular functions of senescent BMSCs models in vitro . Then, the bone-targeted liposomes were designed to encapsulate and deliver senolytics efficiently to senile bone tissue. Based on two aged mice models, we confirmed that bone-targeted delivery of quercetin efficiently eliminated senescent cells in skeleton and enhanced bone formation in vivo, suggesting the bone-targeted elimination of senescent cells is an effective treatment for senile osteoporosis. Graphical abstract: Image, graphical abstract